Enzyme-Linked Immunosorbent Assays for Cholera Serology - Holmgren, J. (1973)
The enzyme-linked immunosorbent assay (ELISA) principle of Engvall and Perlmann, which employs antigen-coated tubes and enzyme-labeled anti-immunoglobulins, was elaborated for use in cholera serology. Immunoglobulin class-specific determinations of primary binding titers of antibodies to cholera exotoxin and endotoxin were more sensitive than were neutralization and vibriocidal tests. It was notable that rather high ELISA titers of immunoglobulin M (IgM) antibodies to exotoxin, which lacked neutralizing capacity were registered, whereas corresponding levels of immunoglobulin G (IgG) antibodies were effectively neutralizing. A modified technique permitting measurement of the binding rate of antibody to the solid-phase antigen was introduced as a possible tool for antibody avidity estimation. Such measurements indicated a wide avidity difference between the IgG and the IgM anti-exotoxin antibodies, which could explain their different neutralizing capacities. The observation that increasing binding rate of the IgG antibodies during the course of the primary immune response could compensate for decreasing antibody amount with regard to neutralizing capacity of serum also indicated the importance of antibody avidity for toxin neutralization. Inhibition with soluble antigen permitted quantitative determination of antigen; levels of exotoxin 0.09 μg/ml and of endotoxin to 1.3 μg/ml were measured.